The effects of cycloprolylglycine and its analogues on brain monoaminergic systems in BALB/c mice - A. A. Abdullina; E. V. Vasileva; V. S. Kudrin; V. B Narkevich; T. A. Gudasheva; K. N. Kolyasnikova; G. I. Kovalev (Фармакокинетика и Фармакодинамика)
Effects of chronic cycloprolylglycine (CPG) and its analogues GZK-001 and GZK-002 treatment at the doses 1 and 2 mg/kg on levels of monoamines and their metabolites in BALB/c mice brain were determined by HPLC. Neurochemical data demonstrated that antidepressant-like effects of the peptides are mediated by an increase in NA and decrease in DA content in frontal cortex. Alterations in striatal monoamine metabolism were observed predominantly after CPG's analogues treatment: the concentration of DA was increased, although its rate of turnover was diminished. In hippocampus more active was CPG: the levels of NE, DA, 5-HT, and its metabolite 5-HIAA were decreased. GZK-001 (1 mg/kg) caused a decrease in the concentration of DA and 5-HIAA. The present results suggest that antidepressant-like effects of CPG and its analogues are associated with DA, NE, and 5-HT systems.